Effect of rosa damascene aromatherapy on anxiety and sleep quality in cardiac patients: A randomized controlled trial. (February 2021) - Jodaki, Kurosh; abdi, Kamel; Mousavi, Masoumeh-Sadat; Mokhtari, Razieh; Asayesh, Hamid; Vandali, Vijayaraddi; Golitaleb, Mohamad
Abstract: Introduction: Anxiety and sleep disorders are the most common disorders of patients admitted to the cardiac care units. The purpose of this study is to investigate the effect of Rosa damascene fragrance on anxiety and sleep quality of hospitalized patients in the cardiac care units. Methods: In this Randomized clinical trial, 60 patients who had the inclusion criteria were conveniently sampled and randomly allocated to the experimental and control groups. Patients were enrolled in the study 24 h after hospitalization. Those diagnosed with dysrhythmia, ACS, and CHF were included. Patient recruitment lasted from October 2018 to December 2019. In these groups, in addition to the routine care, the intervention was performed for three consecutive nights from 22:00 to 06:00. In the experimental group, patients inhaled five drops of Rosa damascene essence 40% in distilled water, while in the control group, patients inhaled five drops of distilled water as placebo. In both groups, anxiety and sleep quality were examined before and after three consecutive nights using the St. Mary's Hospital Sleep Quality Questionnaire (SMHSQ) and the Spiel Berger State-Trait Anxiety Inventory (STAI) questionnaire. Results: The results of this study showed that the use of Rosa damascene aroma in patients hospitalized in the cardiac care unit significantly reduces anxiety and increases the improvement of sleep quality in the experimental group compared to the control group (P < 0.05). The significance level for anxiety and sleep quality was (P = 0.001). Conclusion: Aromatherapy with Rosa damascene reduces anxiety and increases the sleep quality of patients hospitalized in the cardiac care unit. Therefore, along with other treatment measures, Rosa damascene can be used as a complementary method to reduce anxiety and improve sleep quality. Highlights: Inhalation aromatherapy with Rose damascene was assessed in the patients in the cardiac care units. Inhalation aromatherapy with Rose damascene improved sleep quality. Inhalation aromatherapy with Rose damascene improved Anxiety level.